Administrative law : cases, text, and materials - Heckman, Gerald; Van Harten, Gus; Mullan, David J.; Promislow, Janna (Emond Publishing, 2022)
"Administrative law is a required course for all 1L students across Canada. Administrative law deals with the body of law that regulates the ways in which government operates and interacts with its citizens. Administrative Law: Cases, Text and Materials, 8th Edition is designed as a more traditional casebook for use by instructors that approach legal education from a traditional pedagogical approach using lecture and readings."--